Introduction - Alfred Larm Teye (A+BE: Architecture and the Built Environment)
The rate of home-ownership across Europe and in many countries has increased significantly in recent decades. This is partly because most governments have promoted home-ownership as part of an asset-based welfare system with the notion that home-ownership will generate wealth for households through the accumulation of housing equity. Changes in house prices play an important role in the generation of the housing equity and the wealth inherent in home-ownership. In general, house prices change in cycles of upward and downward trends. Each of these cycles may be driven by different sets of fundamental determinants and by the prevailing conditions in the wider economy. Over the long term, home-owners usually accumulate significant housing equity, yielding welfare benefits. However, even periods of brief house price decline can erode the value of housing equity accrued over several years. Following the 2007-08 Global Financial Crisis (GFC), for example, the severe decline in house prices caused many recent home-owners to run into negative equity. Figures from Statistics Netherlands show that following the GFC, in the Netherlands alone the total wealth in residential properties declined from e738,449 million in 2009 to e721,018 million by the end of 2012. In effect, home-ownership involves significant financial risk, which can adversely affect the balance sheets of households. These risks require a better understanding and proper measurements. However, it is also important to first understand house price dynamics, which significantly affect the process of equity generation. A thorough understanding of house price dynamics is necessary if we are to identify innovative ways of insuring against the risks associated with home-ownership.